Evaluation of drug interactions in outpatients taking antipsychotic medications - Alsfouk, Bshra A.; Aljanadi, Qamar M.; Almutairi, Mona M. (Frontiers in Pharmacology, 2025)
IntroductionDrug-drug interactions (DDIs) of antipsychotic medications are clinically significant as they can result in toxicity or treatment failure. This study aims to assess the potential drug-drug and drug-tobacco interactions associated with antipsychotic medications in an outpatient setting. Predictors of antipsychotic DDIs and the impact of potential DDIs on patients’ clinical outcomes were also evaluated in this study.MethodologyA cross-sectional study was conducted on outpatients in King Fahad Medical City in Riyadh, Saudi Arabia between 25 October 2020, and 26 November 2020, who received antipsychotic medications. Data were collected using medical record review. Potential DDIs were assessed using electronic Lexicomp®. The identified potential DDIs were categorized based on risk rating, severity, and reliability rating. Potential adverse effects from interactions were classified by mechanism into pharmacodynamic and pharmacokinetic.ResultsThe study included 220 patients who received 804 drug combinations (i.e., ≥2 drugs concomitantly administered) between antipsychotics and other concomitant drugs. The commonest concomitant classes were antidepressants (20%), anticonvulsants (18%) and cardiovascular agents (15%). The rate of potential DDIs was 71% (n = 574/804). Of the DDIs identified, 92% and 7% were rated C (require monitor therapy) and D (require modify regimen), respectively. In terms of severity level, the majority (n = 552, 96%) of interactions were considered moderate and only 9 interactions were categorized as major. The level of scientific evidence was classified as fair in 64% and as good in 36% of interactions. The majority (91%) involved pharmacodynamic interactions rather than pharmacokinetic mechanisms (9%). The most frequent potential adverse effects were increased sedation (36%), hyperglycemia (15%) and decreased blood pressure (14%). Receiving polypharmacy (i.e., ≥5 drugs concomitantly administered) was significantly associated with an increased probability of drug interaction occurrence (OR = 42, P = 0.0026). Uncontrolled disease state was slightly higher in patients with potential DDIs compared to those with no DDIs (24% vs. 22%, P = 1). Likewise, adverse drug effects were significantly more common in patients with potential DDIs (89% vs. 72%, P = 0.014). The rate of potential drug-tobacco interactions was 6% of patients.ConclusionPotential DDIs of antipsychotic drugs were frequent (71%) and were associated with increased adverse effects. It is crucial for the clinicians to be aware of DDIs, monitor patients closely, and make the appropriate interventions. This emphasizes the importance of enhancing the knowledge about DDIs and the use of reliable AI machines, such as clinical decision support systems, to prevent medication errors.